2016
DOI: 10.1002/lary.25829
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the surgical outcome of preauricular sinus excision techniques

Abstract: SAA could be the preferable technique for preauricular sinus removal. If despite evidence, sinectomy is elected over SAA, microscope use can further decrease recurrence rates comparable to SAA levels. Level of included evidence (Ib-IV) indicates the need for a prospective study comparing surgical outcomes between techniques. Laryngoscope, 126:1535-1544, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Methylene blue is difficult to remove after leakage, resulting in unclear lesion boundaries, very slight distinguishment of the anatomical level, and even residual fistula recurrence. It has been reported that the use of methylene blue in preauricular fistula surgery cannot reduce the risk of postoperative recurrence[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is difficult to remove after leakage, resulting in unclear lesion boundaries, very slight distinguishment of the anatomical level, and even residual fistula recurrence. It has been reported that the use of methylene blue in preauricular fistula surgery cannot reduce the risk of postoperative recurrence[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of preauricular cysts, excision via a supra-auricular approach appears to decrease rates of recurrence compared to techniques such as sinectomy. 1 Additional methods employed in an attempt to adequately excise these cysts/sinuses include ensuring that the tract remains intact, and using a dye to identify the tract. 2 In the setting of peri-parotid atypical mycobacterial infection, Superficial parotidectomy via a facelift or modified Blair incision has been described with adequate removal of granulomatous disease.…”
Section: Discussionmentioning
confidence: 99%
“…Excision via a supra-auricular approach is associated with lower rates of recurrence in comparison to simpler excision techniques such as a sinectomy. [1][2][3] In the setting of peri-parotid atypical mycobacterial infection, parotidectomy via a facelift or modified Blair incision has been described with complete removal of disease. 4 Nevertheless, in lesions that have become recurrently infected, repeatedly excised, or directly involve preauricular skin, complete removal may involve wide local excision (WLE) of overlying skin.…”
Section: Introductionmentioning
confidence: 99%
“…Closing technique depend on the degree of tension and the depth of the defect. 12,13 The reconstruction technique suggested in this paper has the advantage of being applicable to various excision methods, and a flap of healthy tissue is required to cover the scar. Furthermore, because the posterior auricular area has a rich vascular supply, flaps from this area adhere well to other tissue, leading to higher success rates.…”
Section: Discussionmentioning
confidence: 99%
“…11 Bruijnzeel et all. 12 conducted a systematic search from the PubMed and EMBASE databases on March 20, 2015 (Appendix 1). Both title and abstract and full-text screening were based on predefined inclusion and exclusion criteria Fourteen high directness of evidence studies were included.…”
Section: Casementioning
confidence: 99%